Ergonomic design for university classrooms to allow comfort and reduction of fatigue in students and teachers - Párraga Velásquez, Rosario (2014)
This research was conducted in order to meet the ergonomic aspects (posture, furnishings, environmental conditions and security) that affect comfort and fatigue of teachers and students in the university classroom. It was found that stooped posture, computer furniture, noise and chair were the ergonomic aspects that bother teachers while, students discomfort was manifested specifically the seat material, shape and material support. These results merit considering new classrooms with ergonomic design adjustable to the anthropometric dimensions of the teaching equipment and student population.